2010
DOI: 10.1111/j.1755-148x.2010.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐linked barring in chickens is controlled by the CDKN2A /B tumour suppressor locus

Abstract: SummarySex-linked barring, a common plumage colour found in chickens, is characterized by black and white barred feathers. Previous studies have indicated that the white bands are caused by an absence of melanocytes in the feather follicle during the growth of this region. Here, we show that Sex-linked barring is controlled by the CDKN2A ⁄ ⁄ B locus, which encodes the INK4b and ARF transcripts. We identified two non-coding mutations in CDKN2A that showed near complete association with the phenotype. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 41 publications
1
44
0
1
Order By: Relevance
“…We have previously demonstrated that Sex-linked barring is controlled by dominant alleles at the CDKN2A locus, which encodes the alternate reading frame protein (ARF) [3]. We identified four SNPs located within a 12 kb region including CDKN2A exon 1 (Fig 1B).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that Sex-linked barring is controlled by dominant alleles at the CDKN2A locus, which encodes the alternate reading frame protein (ARF) [3]. We identified four SNPs located within a 12 kb region including CDKN2A exon 1 (Fig 1B).…”
Section: Introductionmentioning
confidence: 99%
“…2A) is a classical model for pigment patterning (13, 14). This fascinating sex-linked trait is semi-dominant; homozygous males have wider white bands than heterozygous males, and previous work has implicated both coding and non-coding variation at the CDKN2A/B tumor suppressor locus as a potential cause (14). When the growing feather follicle cylinder was cut open vertically from the posterior side, a chevron-shaped barring pattern was revealed (fig.…”
mentioning
confidence: 99%
“…The results are consistent with a gain-of-function alteration in the CDKN2A/B tumor suppressor locus that causes premature melanocyte progenitor differentiation in a temporally and topologically restricted manner. The genetic defect in Barred Plymouth Rock chickens may cause aberrant feedback control that displays as repetitive stripes (14, fig. S11).…”
mentioning
confidence: 99%
“…This may be then followed by a new wave of melanocytes recruited from a pool of stem cells, which migrate, colonize the feather follicle, produce melanin and form the next black stripe. Thus, the mutations causing sex-related striation in chickens may have an opposite effect than mutations associated with familiar forms of melanoma in humans (HELLSTRÖM et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the locus bar genes, CDKN2B is responsible for melanin activity in melanocytes (CAMPO 1991: DORSHORST & ASHWELL 2009HELLSTRÖM et al 2010). The present study not only extends the knowledge of the epigenetic regulation of autosexing in Polbar chickens but can also contribute information on neoplastic transformations in human melanocytes.…”
Section: Discussionmentioning
confidence: 99%